Birth Certificate As Authentic Evidence Of Children's Origin - Syahrul Bakti Harahap (LEGAL BRIEF, 2022)
Birth certificate is a letter made based on a birth report submitted within a maximum of 60 (sixty) working days for Indonesian citizens, and 10 (ten) working days for foreign nationals. Based on Article 55 Paragraph (1), Law No.1 of 1974, concerning Marriage, it is stated that the origin of a child can only be proven by an authentic birth certificate issued by an authorized official. This study analyzes children born after their mothers are pregnant and newly married, whether the child is legitimate based on an authentic deed issued by local officials in this case is the Population and Civil Registry Office (DUKCAPIL), where the child was born. This study uses a normative juridical legal methodology, only using literature research, while the nature of the research used in this research is descriptive analysis which only describes legal norms, legislation related to Article 55 Paragraph (1) of Law no. 1 of 1974, concerning Marriage. Dance Based on the research that has been done, the legal study of Article 55 Paragraph (1), Law No.1 of 1974, concerning Marriage, the child is a legal child, based on the birth certificate, unless there is a denial from the father who married his mother.